PEMILIHAN PROPOSAL KEGIATAN MAHASISWA WIRAUSAHA MERDEKA TERBAIK MENGGUNAKAN METODE MOORA - Febri Ramadan Nasution; Deci Irmayani; Volvo Sihombing (Politeknik Bisnis Indonesia, 2022)
Entrepreneurial activities in the student environment create business opportunity activities through needs and market analysis. The form of entrepreneurial activity is a direct practice of entrepreneurial learning that has been carried out in a planned and programmed manner, products and services are a manifestation of this program. Based on this, this activity is expected to generate entrepreneurs among students who are able to provide jobs. This study aims to design a decision support system (DSS) for selecting the best independent entrepreneur student activity proposals using the MOORA method. The criteria used are administration, type of business, business location, business plan presentation, and interviews. The three best proposals obtained from the results of this study include: the 1st place was won by the PMWM_01 group with a score of 0.37971, the 2nd place was the PMWM_06 group with a score of 0.37316, and the 3rd place was the PMWM_03 group with a score of 0.37085.